2015
DOI: 10.5005/jp-journals-10015-1310
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Musculoskeletal Disorders among Indian Dentists: A Pilot Survey with Assessment by Rapid Entire Body Assessment

Abstract: Introduction Musculoskeletal disorders (MSDs) are increasingly becoming a nuisance for dental professionals. Nearly, 2 million workers across the world suffer from MSDs each year, with dentists facing an increased risk of developing these ailments. This study is an attempt to assess the risk of MSDs among dental professionals, and eventually to spread awareness regarding the importance of good posture and proper ergonomics. Objectives To determine the presence of MSDs among Indian dentists. Materials and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
11
1
Order By: Relevance
“…Repetitive small ranges of motion involved in dental practice can lead to occupational hazard(s) and its relief is the primary objective of dental ergonomics. 10 In the present study, significant differences were observed between knowledge scores (p=0.01) while awareness scores regarding ergonomics were found to be insignificant. The significant knowledge scores are in agreement to Vyas K et al11 and Desai V et al12 Good awareness regarding ergonomics was seen only among 19.3% of dental interns, and the results are in disagreement to Jadhav HC et al 13 Since ergonomics is not included in the Dental Council of India (DCI) curriculum, therefore such differences in scores were observed while comparing the results of the present study with other studies present in the literature.…”
Section: Discussioncontrasting
confidence: 44%
“…Repetitive small ranges of motion involved in dental practice can lead to occupational hazard(s) and its relief is the primary objective of dental ergonomics. 10 In the present study, significant differences were observed between knowledge scores (p=0.01) while awareness scores regarding ergonomics were found to be insignificant. The significant knowledge scores are in agreement to Vyas K et al11 and Desai V et al12 Good awareness regarding ergonomics was seen only among 19.3% of dental interns, and the results are in disagreement to Jadhav HC et al 13 Since ergonomics is not included in the Dental Council of India (DCI) curriculum, therefore such differences in scores were observed while comparing the results of the present study with other studies present in the literature.…”
Section: Discussioncontrasting
confidence: 44%
“…Several repetitive small ranges of motions are involved in dental practice. 9 Prevention of the occupational hazards is the primary objective of dental ergonomics. Posture reflects the position of an individual which they maintain in space via his bone-muscle-skeletal system.…”
Section: Johcdmentioning
confidence: 99%
“…To assess the risk and exposure of MSDs, Rapid Entire Body Assessment (REBA) score sheet, [5] Quick Exposure Check (QEC) [6] have been used respectively by 10-15 minutes observing each study subject during different dental operating procedures by the researcher. REBA is a postural targeting method for estimating the risks of work related entire body disorders; which gives a rapid, reliable and detailed assessment of the complete body postural risks to any individual who is involved in distinct and repetitive work pattern [7] and the tool QEC assess the exposure to musculoskeletal risk factors of back, shoulders and arms, hands and wrists, and neck before and after an ergonomic intervention. After data collection analysis of data was performed by using SPSS software (Version 22).…”
Section: Methodsmentioning
confidence: 99%